The impact of decentralization on the speed of provision of administrative services in wartime conditions - S. M. Gusarov; N. I. Marchuk (Law and Safety)
The article focuses on the disclosure of the content of administrative services under the impact of decentralisation and the activities of relevant bodies aimed at ensuring human and civil rights and freedoms, interests of legal entities in wartime, and identifying factors affecting the speed of their provision. It has been noted that, in order to improve the quality and speed of administrative service provision in the context of war under the influence of decentralisation, the issue of decentralisation of powers to provide administrative services at the level of local self-government bodies is becoming particularly relevant, in particular through the instruments of delegation, transfer of powers and budget revenues from state bodies to local self-government bodies.